Revealing the Failure Mechanisms of Lithium Metal Solid‐State Batteries with Solid Inorganic Electrolytes by In situ Electron Microscopy - Xiuli Zhang; Haowen Gao; Ming‐Sheng Wang (Advanced Energy & Sustainability Research)
Lithium metal solid‐state batteries (LMSSBs) are considered to be one of the ultimate choices for future energy storage systems because of their high theoretical energy density and enhanced safety. However, the development of LMSSBs has been seriously hindered by some practical issues, such as Li dendrite penetration in the solid‐state electrolytes (SSEs) and uncontrolled interphase growth at the Li/SSE interface, which can cause severe battery degradation, failure, and even safety hazards. To construct safe high‐performance LMSSBs, it is crucial to gain an in‐depth understanding of the failure mechanisms induced by these challenges, especially through direct visualization of the failure processes. In this review, the recent progress on the mechanistic study of LMSSBs by in situ electron microscopy is summarized. In situ transmission electron microscopy (TEM) and scanning electron microscopy (SEM) offer an opportunity to probe the battery failure mechanism by observing the associated physical and chemical processes at nano/atomic resolution. The failure causes of Li dendrites growth and interphase formation are classified and discussed, followed by the corresponding solutions to address these issues. Additionally, the emerging perspectives on future research directions in this field are also summarized.